Analisis Pengembangan Konsep Dasar Kepemimpinan Rektor Universitas Islam Negeri (UIN) Malang Periode Tahun 1998 s.d 2008 - Yunus, Jamal Lulail (Universitas Brawijaya, Indonesia, 2009)
This Study specifically analyses the structure of the leadership basic concept which developed by the Rector of the State Islamic University (UIN) of Malang from 1998 to 2008 in order to develop the higher Islamic university he led. This is basing on the developmental phenomena of UIN Malang which is institutionally changing, the disciplines paradigm of combining science and Islam, and the highly improving physical structure development. This research applies positivistic qualitative approach focusing on the leadership reality in UIN Malang which proceeds dynamically as being proposed by Giddens (1974). Conceptually, this research is a field research using the technique of on going analysis approach combined with content analysis approach proposed by Krippendorff through Blumer's symbolic interaction approach. This research focused on finding the answer of leadership basic concept, a leader's performance dimensions, and a leadership style that developed by the Rector of UIN Malang from 1998 to 2008. The research reveals that the structure of leadership basic concept developed by the Rector of UIN Malang from 1998 to 2008, which the researcher names as as Ulul Albab Leadership Concept, cocisist of: (1) the Basic Concept of Ulul Albab Leadership Model involving the principles of dzikir, thought and good deed; (2) the Performance Dimension of Ulul Albab Leadership Model possesses the character strength in the form of spiritual deepness, ethical conduct, science broadness and professional maturity; (3) the Ulul Albab Leadership Style adapts love approach, leadership by examples approach, appreciation approach and also brotherhood and humanity approach, all of which lead to the service values.